Urgensi Dan Relevansi Pelibatan Pemangku Kepentingan Dalam Perencanaan Pendidikan - Kartika, Mirna; Sirozi, Muhammad (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the urgency and relevance of stakeholder engagement in the context of education planning. Stakeholders, such as teachers, students, parents, communities, governments and various other relevant parties, have an important role to play in creating an inclusive, sustainable and responsive educational environment to the needs of society. The research method carried out in this article is the literature method, where the author critically examines the thoughts of figures and literature of books, journals, and those related to each other which are indeed in accordance with the material to be presented. Involving them in the educational planning process can improve the quality of educational programs, strengthen community support, and create sustainable engagement. By having a common agreement on the goals, strategies and evaluation of education programs, stakeholder engagement can strengthen transparency, accountability and participation in education decision-making. It also ensures that the various perspectives and needs of stakeholders are thoroughly considered, so that the resulting educational programs are more relevant, effective and have a positive impact on the entire educational community. Thus, this article underscores the importance of urgency and relevance of stakeholder involvement in education planning as an effort to create an education system that is inclusive, sustainable, and oriented to the needs of society as a whole. Involving stakeholders in education planning is a crucial aspect in ensuring the success and sustainability of education programs.